2016
DOI: 10.1371/journal.pone.0148697
|View full text |Cite
|
Sign up to set email alerts
|

Intake and Biomarkers of Folate and Risk of Cancer Morbidity in Older Adults, NHANES 1999-2002 with Medicare Linkage

Abstract: BackgroundAfter the 1998 mandatory folic acid fortification of enriched cereal-grain products in the U.S., safety concerns were raised that excess consumption of folic acid and high blood folate biomarkers detected in adults may increase the risk of certain types of cancer.MethodsBaseline data from about 1400 participants in the National Health and Nutrition Examination Survey (NHANES) 1999–2002, aged ≥ 57 years were linked to Medicare and mortality files through December 31, 2007. Using cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Although it is still debatable whether homocysteine is a causal factor or a marker of CVD and mortality ( 25 ), others have shown that supplementation with folic acid decreased the risk of CVD, especially stroke ( 3 ). There was no significant association between RBC folate concentration and all-cause and cardiovascular mortality—a finding, similar to some studies ( 26–31 ) but not others ( 3 , 32–34 ). To the best of our knowledge, the effect of folate on all-cause and cardiovascular mortality has not been investigated in a very old population and the possibility of an age group-specific effect cannot be discounted.…”
Section: Discussionsupporting
confidence: 88%
“…Although it is still debatable whether homocysteine is a causal factor or a marker of CVD and mortality ( 25 ), others have shown that supplementation with folic acid decreased the risk of CVD, especially stroke ( 3 ). There was no significant association between RBC folate concentration and all-cause and cardiovascular mortality—a finding, similar to some studies ( 26–31 ) but not others ( 3 , 32–34 ). To the best of our knowledge, the effect of folate on all-cause and cardiovascular mortality has not been investigated in a very old population and the possibility of an age group-specific effect cannot be discounted.…”
Section: Discussionsupporting
confidence: 88%
“…Although our results differ from several studies [8,14], they are largely in agreement with a number of reports [9,[15][16][17]. Although the underlying mechanisms by which lower folate status contributes to mortality remain unclear, some possible explanations could be considered.…”
Section: Discussionsupporting
confidence: 76%
“…Those authors did not find significant associations between the presence of non-metabolized FA, intake of naturally-occurring food folate or FA separately, and cancer incidence [50]. …”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a recent study with more than 1400 older adults (≥57 years) with a median follow-up of 6.3 years showed that high total folate intake appear to be protective against cancer in post-FA fortification years. Those authors did not find significant associations between the presence of non-metabolized FA, intake of naturally-occurring food folate or FA separately, and cancer incidence [ 50 ].…”
Section: Discussionmentioning
confidence: 99%